Inducible Human Endothelin-1 Overexpression in Endothelium Raises Blood Pressure via Endothelin Type A Receptors. Issue 2 (August 2015) - Rautureau, Yohann; Coelho, Suellen C.; Fraulob-Aquino, Julio C.; Huo, Ku-Geng; Rehman, Asia; Offermanns, Stefan; Paradis, Pierre; Schiffrin, Ernesto L.
Abstract : The mechanisms of blood pressure regulation by endothelin-1 produced by endothelial cells are complex and still unclear. Transgenic mice with endothelium-restricted human endothelin-1 ( EDN1 ) overexpression presented vascular damage but no significant change in blood pressure, which could be because of adaptation to life-long exposure to elevated endothelin-1 levels. We now generated a tamoxifen-inducible endothelium-restricted EDN1 overexpressing transgenic mouse (ieET-1) using Cre/loxP technology. Sixteen days after tamoxifen treatment, ieET-1 mice presented ≥10-fold increase in plasma endothelin-1 ( P <0.01) and ≥20 mm Hg elevation in systolic blood pressure ( P <0.01), which could be reversed by atrasentan ( P <0.05). Endothelin-1 overexpression did not cause vascular or kidney injury or changes in kidney perfusion or function. However, endothelin type A and B receptor expression was differentially regulated in the mesenteric arteries and the kidney. Our results demonstrate using this ieET-1 mouse model that 21 days of induction of endothelin-1 overexpression caused endothelin-1–dependent elevated blood pressure mediated by endothelin type A receptors. Abstract : Supplemental Digital Content is available in the text.